Prospective validation of a novel renal activity index of lupus nephritis. (August 2017) - Gulati, G; Bennett, M R; Abulaban, K; Song, H; Zhang, X; Ma, Q; Brodsky, S V; Nadasdy, T; Haffner, C; Wiley, K; Ardoin, S P; Devarajan, P; et al.
Objectives: The renal activity index for lupus (RAIL) score was developed in children with lupus nephritis as a weighted sum of six urine biomarkers (UBMs) (neutrophil gelatinase-associated lipocalin, monocyte chemotactic protein 1, ceruloplasmin, adiponectin, hemopexin and kidney injury molecule 1) measured in a random urine sample. We aimed at prospectively validating the RAIL in adults with lupus nephritis. Methods: Urine from 79 adults was collected at the time of kidney biopsy to assay the RAIL UBMs. Using receiver operating characteristic curve analysis, we evaluated the accuracy of the RAIL to discriminate high lupus nephritis activity status (National Institutes of Health activity index (NIH-AI) score >10), from low/moderate lupus nephritis activity status (NIH-AI score ≤10). Results: In this mixed racial cohort, high lupus nephritis activity was present in 15 patients (19%), and 71% had proliferative lupus nephritis. Use of the identical RAIL algorithm developed in children resulted in only fair prediction of lupus nephritis activity status of adults (area under the receiver operating characteristic curve (AUC) 0.62). Alternative weightings of the six RAIL UBMs as suggested by logistic regression yielded excellent accuracy to predict lupus nephritis activity status (AUC 0.88). Accuracy of the model did not improve with adjustment of the UBMs for urine creatinine or albumin, and was little influenced by concurrent kidney damage. Conclusions: The RAIL UBMs provide excellent prediction of lupus nephritis activity in adults. Age adaption of the RAIL is warranted to optimize its discriminative validity to predict high lupus nephritis activity status non-invasively.